Ligand-Based and Structured-Based In Silico Repurposing Approaches to Predict Inhibitors of SARS-CoV-2 Mpro Protein - Alfredo Juárez-Saldívar; Edgar E. Lara-Ramírez; Francisco Reyes-Espinosa; Alma D. Paz-González; Juan Carlos Villalobos-Rocha; Gildardo Rivera (MDPI AG, 2020)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a coronavirus that causes the pandemic Coronavirus Disease 2019 (COVID-19). There is no current specific treatment for this new coronavirus. In this study, we employed a virtual screening repurposing strategy to search for potential SARS-CoV-2 Mpro inhibitors. The databases PDB, ChEMBL, BindingDB and DrugBank were queried with several filtering steps based on ligand-based and structure-based approaches. As a result, we obtained 58 molecules (37 from ChEMBL and 21 from DrugBank) that potentially inhibit SARS-CoV-2 Mpro. These molecules have on their chemical structure functional groups that favor stronger docking scores than the inhibitor N3. Several of these molecules are reported experimentally as SARS-CoV Mpro inhibitors. Hence, a combined virtual screening strategy allowed finding chemical compounds with a high potential for the inhibition of SARS-CoV-2 Mpro.